IMPLEMENTATION OF PROJECT-BASED LEARNING BASED ON ECOPEDAGOGY AS A STRATEGY TO STRENGTHEN THE PROFILE OF PANCASILA STUDENTS IN THE MERDEKA CURRICULUM - Rohsulina, Pranichayudha; Deristani, Anggun; Rahman, MS Khabibur; Sunarhadi, Muhammad Amin; Aji, Bayu Kurnia (GeoEco, 2026)
Social Studies (IPS) learning in junior high schools in Sukoharjo Regency is challenged by students’ low ecological awareness, limited variation in learning models that encourage active engagement, and the suboptimal implementation of the Merdeka Curriculum integrated with the Pancasila Student Profile. These conditions result in a lack of critical thinking, creativity, and environmental awareness among students. This study aims to develop a Project-Based Learning–Ecopedagogy (PJBL_EP) model as an alternative instructional strategy to strengthen the Pancasila Student Profile at the junior high school level. The research employs a Research and Development (R&D) method, referring to the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects involved teachers and students from JHS 3 Nguter, JHS 5 Sukoharjo, and JHS Muhammadiyah Kartasura, with an extended trial involving 40 Social Studies teachers from 12 sub-districts in Sukoharjo Regency. The PJBL_EP model is designed through the integration of project-based learning with ecopedagogy principles, emphasising ecological awareness, critical thinking, creativity, independence, collaboration, and noble character development. Validation results showed an excellent feasibility score (92; 88.75; and 91.67). Field trials identified challenges in teachers’ mastery of content, classroom management, and students’ literacy; however, improvements in syntax, group management, and teaching modules enhanced practicality. Overall, PJBL_EP effectively makes Social Studies learning more contextual, creative, and environmentally oriented, while simultaneously strengthening the values of the Pancasila Student Profile.